ENHANCING THE STUDENTS’ WRITING SKILL THROUGH MOZAIC ACTIVITY - elisa; Nofriati, Eli (Journal of English Education and Social Science, 2023)
The aimed of this research is to find out does the use of MOZAIC Activity to improve students’writing skill or not. The research conducted at MTsS Peulimbang with classroom action research design which conducted in two cycle by following the procedure of the action research consisting of foursteps; planning, implementing, observing and reflecting. Each cycle was carry out in three meeting. The subject of the research was the second year students class 2/I of MTsS Peulimbang. The research instruments used in this research were test, observation checklist and questionnaire. The obtained data were presented and analyzed in qualitative and quantitative data. The result of this research showed that Mozaik Activity could improve the students’ skill in learning writing. It could be proved by some research finding found by the researcher. The first result found from the test given to the students. The students’ average score of the test in cycle 1 was 65.25 and it increased to 78.6 in cycle 2. The second result was obtained from the observation of the researcher’s performance and students’ activities. The percentage of the researcher’s performance in the first cycle was 68.75% or in level good. While, in the second cycle it increased to 87.5% or in level very good criterion. Next, the percentages of the students’ activities was 66.23% or in level enough in the first cycle and it increased to be 85% or in very good criterion in the second cycle. The other finding got from the result of questionnaire. It showed that the students gave positive responses toward the implementing Mozaik Activity in learning writing. It could be seen by the result of the questionnaire was 3.62 or in category strongly agree. It means that the students’ response was very good.